Reducing postural load in order picking through a smart workwear system using real-time vibrotactile feedback. (November 2020) - Lind, Carl Mikael; Yang, Liyun; Abtahi, Farhad; Hanson, Lars; Lindecrantz, Kaj; Lu, Ke; Forsman, Mikael; Eklund, Jörgen
Abstract: Vibrotactile feedback training may be one possible method for interventions that target at learning better work techniques and improving postures in manual handling. This study aimed to evaluate the short term effect of real-time vibrotactile feedback on postural exposure using a smart workwear system for work postures intervention in simulated industrial order picking. Fifteen workers at an industrial manufacturing plant performed order-picking tasks, in which the vibrotactile feedback was used for postural training at work. The system recorded the trunk and upper arm postures. Questionnaires and semi-structured interviews were conducted about the users' experience of the system. The results showed reduced time in trunk inclination ≥20°, ≥30° and ≥45° and dominant upper arm elevation ≥30° and ≥45° when the workers received feedback, and for trunk inclination ≥20°, ≥30° and ≥45° and dominant upper arm elevation ≥30°, after feedback withdrawal. The workers perceived the system as useable, comfortable, and supportive for learning. The system has the potential of contributing to improved postures in order picking through an automated short-term training program. Highlights: The effectiveness of the Smart Workwear System was evaluated for posture improvements. Direct vibrotactile feedback was used to train 15 manufacturing employees. The system contributed to reduce adverse postures for the trunk and the upper arm. The system contributed to reduce adverse postures both during and after use. The system was perceived as useable, comfortable and supportive for learning.